2018
DOI: 10.1242/jeb.188532
|View full text |Cite
|
Sign up to set email alerts
|

Orienting to polarized light at night—matching lunar skylight to performance in a nocturnal beetle

Abstract: For polarized light to inform behaviour, the typical range of degrees of polarization observable in the animal's natural environment must be above the threshold for detection and interpretation. Here, we present the first investigation of the degree of linear polarization threshold for orientation behaviour in a nocturnal species, with specific reference to the range of degrees of polarization measured in the night sky. An effect of lunar phase on the degree of polarization of skylight was found, with smaller … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Because our estimation of reliable coding does not account for DoPs between the discrete values that were tested (0.35, 0.1 and 0.05), and based on the significance of responses of individual neurons, we assume that at least for TL3-, CL1a- and CPU neurons the actual threshold for AoP coding might be lower than the estimated threshold and might lie between 0.35 and 0.1. The low thresholds found in TL2 and TB1 neurons are similar to thresholds that have been determined for polarotactic behavior in honeybees, crickets, and dung beetles (von Frisch 1967 ; Henze and Labhart 2007 ; Foster et al 2019 ) and for neuronal responses of polarization-opponent interneurons in the optic lobes of crickets (Labhart 1996 ). Prior to this study, neurons of the CX have been tested with different DoPs only in crickets (CNL neurons, Sakura et al 2007 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Because our estimation of reliable coding does not account for DoPs between the discrete values that were tested (0.35, 0.1 and 0.05), and based on the significance of responses of individual neurons, we assume that at least for TL3-, CL1a- and CPU neurons the actual threshold for AoP coding might be lower than the estimated threshold and might lie between 0.35 and 0.1. The low thresholds found in TL2 and TB1 neurons are similar to thresholds that have been determined for polarotactic behavior in honeybees, crickets, and dung beetles (von Frisch 1967 ; Henze and Labhart 2007 ; Foster et al 2019 ) and for neuronal responses of polarization-opponent interneurons in the optic lobes of crickets (Labhart 1996 ). Prior to this study, neurons of the CX have been tested with different DoPs only in crickets (CNL neurons, Sakura et al 2007 ).…”
Section: Discussionsupporting
confidence: 80%
“…For A. mellifera a detection threshold was proposed at a DoP between 0.07 and 0.1 (von Frisch 1967 ), and field crickets ( Gryllus campestris ) showed behavioral responses at DoPs even lower than 0.07 (Henze and Labhart 2007 ). Findings for the nocturnal dung beetle ( Scarabaeus satyrus ) indicated a behavioral threshold for polarized lunar skylight between 0.04 and 0.32 (Foster et al 2019 ). These studies show that certain insect species can utilize polarization information for orientation even under highly unfavorable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it might explain why flight duration was not significantly affected by clouds in front of the moon since the polarization pattern extends over the whole sky and is therefore not shielded completely by scattered clouds 29 . For dung beetles it has been already shown that they are capable of using the polarization signal for navigation 16,30,31 and it has been proposed that moths might be capable of utilizing the same signal 32 . At the same time, it has already been demonstrated that urban skyglow can diminish the lunar polarization signal 33 , making a detailed investigation of the interplay between these two factors and the significance for moth orientation particularly exciting to understand underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the DoP threshold is also used by animals in their orientation behavior. The polarized light that can be detected by animals must be above the threshold that is able to be perceived [49]. The results mentioned above suggested the DoP decreased as the obscuration ratio increased.…”
Section: Dop Changes During Eclipsementioning
confidence: 92%